LeaderTICE: A Platforms Recommendation System Based on a Comparative and Evaluative Study of Free E-learning Platforms - Ouadoud, Mohammed; Chkouri, Mohamed Yassin; Nejjari, Amel (International Journal of Online and Biomedical Engineering (iJOE), 2018)
E-learning platforms are constantly changing; they have transformed the life of teachers and students. In this paper, we propose a comparative study of free e-learning platforms, from a methodical and systemic approach that identifies the dimensions, the specifications and the essential criteria for evaluating platforms. In addition, we evaluate the most recognized e-learning platforms in order to measure the match degree between technological possibilities that they offer and the pedagogical training assumptions. Eventually, we exploit the obtained results for the recommendation of free e-learning platforms since the LeaderTICE system that we implemented, in order to facilitate the choice of the most suitable e-learning platform to help the users in their choice to benefit of the potential offered by technologies in pedagogy